Boundary Integral Technique of 2nd Order Partial Differential Equation by Using Radial Basis. (20th July 2022) - Asghar, A.; Ahmad, M. O.; Bashir, M. N.; Muhammad, Taseer; Khan, Sami Ullah; Ramzan, M.
Abstract : The solution of second order partial differential equation, with continuous change in coefficients by the formation of integral equation and then using radial basis function approximation (RBSA), has been developed in this paper. Use of boundary element method (BEM), which gives the solution of heat or mass diffusion in non-homogenous medium with function varying smoothly in space is also the part of this article. Discretization of boundary of integral domain instead of entire domain of the problem concerned is also the distinction of the recent work. The numerical solution of some problems with known value of the variable has also been included at the end.